Composite Materials for Draft Line Insulators - Sh. Banashak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Filled composite materials on the basis of ethylene-propylene-diene rubber and epoxy resin, their ageing process have been investigated under conditions of humid warm climate and in the device of Xenotest-type. The paper shows an influence of ageing aspect on changes in a number of material indices.